2016
DOI: 10.1177/1356336x16641024
|View full text |Cite
|
Sign up to set email alerts
|

Parental influence on the physical activity of Chinese children

Abstract: This study aimed to examine the association among parental moderate-to-vigorous physical activity (MVPA), parental support, and the MVPA of children by gender. Participants comprised of 172 boys and 151 girls aged seven to 11 years old from three primary schools in Shanghai. Their parents were also included as research respondents. Accelerometers were utilized to measure MVPA duration among the children. Questionnaires that focused on parental support and MVPA were completed by the parents. Results indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 57 publications
4
21
0
Order By: Relevance
“…In a study of fifth grade students from Germany, Schoeppe et al [30] confirmed the same-sex imitation hypotheses by finding relationships between girls’ leisure-time physical activity and maternal sport participation and between boys’ activity and paternal sport participation. Similar results were found by Lijuan et al [31] in Chinese children, by Kirby et al [32] in Scottish adolescents, and by Cheng et al [33] in Brazilian adolescents. Another study from Germany reported positive relationships of social support and social modelling from parents and moderate-to-vigorous physical activity (MVPA) in elementary school children and also emphasised gender differences in MVPA, but did not analyse parental influences on MVPA separately for both genders [27].…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…In a study of fifth grade students from Germany, Schoeppe et al [30] confirmed the same-sex imitation hypotheses by finding relationships between girls’ leisure-time physical activity and maternal sport participation and between boys’ activity and paternal sport participation. Similar results were found by Lijuan et al [31] in Chinese children, by Kirby et al [32] in Scottish adolescents, and by Cheng et al [33] in Brazilian adolescents. Another study from Germany reported positive relationships of social support and social modelling from parents and moderate-to-vigorous physical activity (MVPA) in elementary school children and also emphasised gender differences in MVPA, but did not analyse parental influences on MVPA separately for both genders [27].…”
Section: Introductionsupporting
confidence: 89%
“…Focussing on gender differences in the provision of social support, Hoefer et al [35] found parents being more likely to transport boys to physical activity locations than girls. However, in a recent study of 11-year old children from Shanghai [36] no gender differences in terms of logistic support and explicit modelling for physical activity of parents were observed.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, previous studies conducted in the US, Germany and Scotland reported that compared to boys, girls might receive less peer support for PA, and they might be engaging in more 'non-physically active' activities with their peers [8,10,14]. However, studies conducted in China reported that parents do not differentiate between sons and daughters when providing support [33,34], suggesting that some cross-cultural differences may exist.…”
Section: Discussionmentioning
confidence: 82%
“…Substantial evidence indicated that girls were less active than boys [67, 68]. The main reason was that activeness, bravery, aggressiveness, and perseverance are valued more in boys than in girls while gentleness, kindness, approachability, sensitivity, quietness, weakness, and malleability are valued in girls [69]. Moreover, secondary school students are entering their teenage years, a period characterised by increasing sex differences.…”
Section: Discussionmentioning
confidence: 99%